306 - Robotic cystectomy and ileal conduit for neurogenic bladder - Peyronnet, B; Paris, H; Haudebert, C (Continence (Amsterdam), 2025)
Patients with neurological disorders are at risk of having vesicosphincteric symptoms that are refractory to first-line treatments. In such cases, a surgical intervention such as Enterocystoplasty for bladder enlargement may be proposed. This type of surgery was mostly performed through open surgery, but it is now possible to offer it through minimally invasive surgery with the help of a robotic surgical system. We present the case of a young patient with spina bifida who presents with symptoms of bladder hyperactivity that did not improve with first-line treatments. A laparoscopic robot-assisted enterocystoplasty for bladder enlargement is proposed for the patient. The patient is positioned in a supine position. A laparoscopic transperitoneal approach is performed. The Da Vinci robot is placed on the operating table. Initially, a supratrigonal cystectomy is performed, followed by the resection of 40 cm of ileum after visualization of the mesenteric vasculature using an indocyanine green injection. The W-shaped enterocystoplasty is then created and sutured to the trigone. Finally, an artificial urinary sphincter is implanted. The procedure was fully performed using robot-assisted laparoscopic surgery. Enterocystoplasty after supratrigonal cystectomy for neurogenic bladder by robot-assisted laparoscopy is a technique that could reduce postoperative morbidity in these vulnerable patients. Funding No one Clinical Trial No Subjects Human Ethics not Req'd It's not a study Helsinki Yes Informed Consent Yes